PENERAPAN METODE TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN KECERDASAN EMOSIONAL ANAK PADA SISWA KELAS V SD MUHAMMADIYAH AMBARKETAWANG 2 - Usi Usmarani; Muhammad Ragil Kurniawan (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2018)
Many students experience emotional intelligence problems. This is seen in students who prefer to disturb their friends during the learning process, are angry with the teacher when given advice. Many also cannot regulate their moods like often shouting in class, so they cannot control their emotions when they are angry and upset both at their friends and their teachers. The application of the Teams Games Tournament (TGT) is expected to increase children's emotional intelligence, therefore this study aims to determine the increase in emotional intelligence using the application of the Teams Games Tournament (TGT) in fifth grade students of SD Muhammadiyah Ambarketawang 2. This research was included in a class action research consisting of two cycles. The subject of this study was fifth grade students of Muhammadiyah Ambarketawang Elementary School 2. The object of this research was SD Muhammadiyah Ambarketawang 2. This data collection technique was in the form of observation, questionnaires, and documentation. Data analysis used qualitative and quantitative analysis. The results showed that there was an increase in children's emotional intelligence using the Teams Games Tournament (TGT) method. Increased emotional intelligence can be seen from the acquisition of the pretest percentage score of 43.75%, after the action results of the percentage score of the first cycle to 68.75%, while the results of the percentage cycle II score to 81.25% included in the excellent category. Students can understand and be able to manage emotions well, there is mutual respect between friends, there is an increase in motivation in students, and students can establish good relations with others. The results of this study indicate that emotional intelligence can be improved through the Teams Games Tournament (TGT) method.